Empowered Voices: Exploring Women's Autonomy And Fertility Intention In Indonesia - Muthia, Azka; Setyonaluri, Diahhadi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study explores the relationship between women's autonomy and fertility intentions in Indonesia, considering the socio-cultural and economic dynamics that shape reproductive decision-making. Utilizing couples’s data from the 2017 Indonesia Demographic and Health Survey (IDHS), the study employs an instrumental variable (IV) approach to address potential endogeneity in measuring women's autonomy. The findings reveal that higher levels of women's autonomy, defined through participation in household decision-making, significantly reduce women's fertility intentions. Women with autonomy have a stronger ability to negotiate reproductive decisions with their husbands, enabling them to align their reproductive choices with their personal aspirations. Having autonomy enables women to exercise their reproductive rights and make well-informed decisions about family planning. In contrast, limited autonomy restricts women’s participation in decision-making, reinforcing social norms that prioritize male authority in fertility-related matters. Closing this gap requires targeted interventions to enhance women’s role in reproductive health, ensuring they have an equal say in fertility-related decisions.